Task errors contribute to implicit aftereffects in sensorimotor adaptation - Leow, L.; Marinovic, Welber; de Rugy, A.; Carroll, T. (Wiley-Blackwell, 2018)
Perturbations of sensory feedback evoke sensory prediction errors (discrepancies between predicted and actual sensory outcomes of movements), and reward prediction errors (discrepancies between predicted rewards and actual rewards). When our task is to hit a target, we expect to succeed in hitting the target, and so we experience a reward prediction error if the perturbation causes us to miss it. These discrepancies between intended task outcomes and actual task outcomes, termed “task errors,” are thought to drive the use of strategic processes to restore success, although their role is incompletely understood. Here, as participants adapted to a 30° rotation of cursor feedback representing hand position, we investigated the role of task errors in sensorimotor adaptation: during target-reaching, we either removed task errors by moving the target mid-movement to align with cursor feedback of hand position, or enforced task error by moving the target away from the cursor feedback of hand position, by 20–30° randomly (clockwise in half the trials, counterclockwise in half the trials). Removing task errors not only reduced the extent of adaptation during exposure to the perturbation, but also reduced the amount of post-adaptation aftereffects that persisted despite explicit knowledge of the perturbation removal. Hence, task errors contribute to implicit adaptation resulting from sensory prediction errors. This suggests that the system which predicts the sensory consequences of actions via exposure to sensory prediction errors is also sensitive to reward prediction errors.